Publishing industry in institutions of higher education of Kazakhstan (Herald of Journalism, 2016)
The article considers the technology in the publishing industry and their location in regions and facing some difficulties in types of publishing houses. In the article were discussed impact of digital printing onpublishing houses of institutions of higher education and superiority and disadvantages of digital printing, advantages of publishing houses of institutions of higher education in printing books.
Keywords: publishing industry of institutions of higher education; technology; digital printing